Metaphors in the dictionary of German football language - R. V. Beliutin (Вестник Самарского университета: История, педагогика, филология)
The article is devoted to comprehensive analysis of metaphors in German football language found in an extraordinary specialized dictionary, which was edited by a German linguist A. Burkhardt. Metaphor is viewed as a vitally important conceptual and language mechanism that helps understand the essence of complex objects, phenomena, events – in this very case belonging to football discourse, emphasize new dimensions of football concepts, introduce imagination and evaluation in the speaker’s utterance. The conducted analysis makes it possible to conclude that the German football discourse is highly metaphorical, capable of correlating with diverse conceptual spheres serving as source domains («war», «religion», «mechanisms», «flora», «fauna», «medicine», «arts», «construction» and others). Resources of sports discourse itself are also actively employed, which entails import of concepts inside the discourse – for example, boxing or track-and-field athletics terms are applied to determine football realia. The status of metaphors in the German football language and their firm position in this communicative space are distinguished through an outstanding network of synonymous constructions and variations, multifarious word-building patterns (mainly compounding) in developing new metaphoric units. The linguistic insight into the metaphoric football language is complemented by translation and linguodidactics planes: typology of variants for relating football metaphors from one language to another (by the example of the German and Russian languages) allows to reveal zones of similarity and difference in metaphoric conceptualization of football realia in different world views, to identify the nature of possible difficulties for interpreters working in this professional sphere and those studying football language for communication, to understand the contents in sports media and so on. The methods used are discourse analysis, modeling, classification, lexicographic, distributive, comparative and contrastive methods.